2-Hydroxyglutarate Metabolism Is Altered in an in vivo Model of LPS Induced Endotoxemia - Fitzpatrick, Susan F.; Lambden, Simon; Macias, David; Puthucheary, Zudin; Pietsch, Sandra; Mendil, Lee; McPhail, Mark J. W.; Johnson, Randall S. (Frontiers in Physiology, 2020)
The metabolic response to endotoxemia closely mimics those seen in sepsis. Here, we show that the urinary excretion of the metabolite 2-hydroxyglutarate (2HG) is dramatically suppressed following lipopolysaccharide (LPS) administration in vivo, and in human septic patients. We further show that enhanced activation of the enzymes responsible for 2-HG degradation, D- and L-2-HGDH, underlie this effect. To determine the role of supplementation with 2HG, we carried out co-administration of LPS and 2HG. This co-administration in mice modulates a number of aspects of physiological responses to LPS, and in particular, protects against LPS-induced hypothermia. Our results identify a novel role for 2HG in endotoxemia pathophysiology, and suggest that this metabolite may be a critical diagnostic and therapeutic target for sepsis.